Effects of Arginine-calcium carbonate pretreatment on the remineralizing and bonding performance of phosphorylated dentin. (April 2023) - Ding, Jingyu; Zhu, Xuanyan; Lin, Qi; Lin, Lingkang; Yang, Zhengyuan; Zhu, Song
Abstract: Objectives: To evaluate the effects of Arginine-calcium carbonate (Arg-CaCO3 ) paste treatment of phosphorylated dentin on remineralizing and bonding performance during direct and indirect restorations under pulpal pressure. Methods: Under simulated pulpal pressure, dentin of healthy third molars were abraded and acid etched for 15s, then randomly divided into 4 groups: negative control group; Arg-CaCO3 group (1min); 2.5% Sodium trimetaphosphate (STMP) group (3min); S-A group, 2.5% STMP + Arg-CaCO3 . After 24h, remineralization and dentin tubular occlusion were assessed by Attenuated total reflection fourier transform infrared spectroscopy (ATR-FTIR), Micro-Raman spectroscopy, Vickers hardness, Field-emission scanning electron microscope (FESEM) and Energy X-ray dispersive spectrometer (EDS). The liquid environment was the simulated body fluid (SBF) permeated from dentin tubules due to pulpal pressure. Stick specimens prepared with self-etch dentin adhesive were tested for microtensile bond strength (μTBS) and interfacial silver nanoleakage on both immediate direct restoration and indirect restoration with a 7-day temporary period. Data were analyzed by the Kruskal-Wallis test, Mann-Whitney test, Welch ANOVA or one-way ANOVA and Tukey post hoc test (p < 0.05). Results: The pretreatment of 2.5% STMP with Arg-CaCO3 significantly increased relative mineral content by ATR-FTIR, Raman and FESEM-EDS, simultaneously enhancing dentin tubular occlusion (%) and mechanical property to the most considerable extent. Furthermore, the pretreatment significantly promoted the μTBS of indirect restoration and reduced nanoleakage after 7 days. Conclusions: The application of Arg-CaCO3 paste on phosphorylated dentin could improve intra- and extra-tubular mineralization and the stability of adhesion interface. Clinical relevance: Without exceeding the amount of conventional tooth preparation, combining 2.5% STMP with Arg-CaCO3 paste before the self-etch bonding system might be a promising clinical strategy to relieve dentin hypersensitivity and strengthen bonding performance efficiently and conveniently.